Hemodynamic and Molecular Effects of F-43 in Experimental Hypertension - Abdurazakova, Ikbolkhon; Zaynabiddinov, Anvar; Abdullaev, Izzatullo; Gayibov, Ulugbek; Ziyoyiddinov, Ziyodullo; Maxmudov, Lazizbek; Zhurakulov, Sherzod (Trends in Sciences, 2026)
Hypertension is closely associated with impaired calcium regulation in vascular smooth muscle, leading to sustained vasoconstriction and elevated peripheral resistance. This study investigates the hemodynamic activity of a newly synthesized tetrahydroisoquinoline derivative, F-43 (1-(4′-methoxyphenyl)-6,7-dimethoxy-1,2,3,4-tetrahydroisoquinoline), produced via a modified Pictet–Spengler reaction. Hemodynamic responses were assessed in conscious rats (n = 3 per group) using tail-cuff plethysmography at doses of 25 and 50 mg/kg, including evaluation in an adrenaline-induced hypertension model. F-43 produced a mild transient rise in arterial pressure followed by a statistically significant normalization phase (p-value < 0.05), demonstrating a modulatory rather than purely hypotensive profile. In the adrenaline-induced model, F-43 (50 mg/kg) significantly reduced systolic and diastolic elevations within three hours (p-value < 0.01), restoring values close to baseline. No acute adverse effects or behavioral abnormalities were observed at the tested doses. To explore potential mechanisms, simplified molecular docking screening was performed, showing favorable binding energies (–6.4 to –8.7 kcal/mol) toward key calcium-handling proteins, suggesting possible interaction with Cav1.2, SERCA, RyR2, and NCX. These in silico findings support the hypothesis that F-43 may influence intracellular Ca²⁺ flux, consistent with the observed hemodynamic effects. In conclusion, F-43 demonstrates a unique vascular tone–stabilizing effect, statistical efficacy in an acute hypertension model, and an acceptable preliminary safety profile. The compound represents a promising novel lead molecule for further development of calcium-modulating antihypertensive agents. HIGHLIGHTS A novel tetrahydroisoquinoline derivative (F-43) was synthesized via a modified Pictet–Spengler reaction. F-43 exhibited a vascular tone–stabilizing effect rather than a purely hypotensive response in conscious rats. The compound significantly attenuated adrenaline-induced systolic and diastolic hypertension within 3 hours. GRAPHICAL ABSTRACT